Efficacy of 5-aminolevulinic acid-mediated photodynamic therapy using light-emitting diodes in human colon cancer cells - HATAKEYAMA, TOMOYA (D.A. Spandidos, 2013)
5-Aminolevulinic acid (ALA)-mediated photodynamic therapy (PDT) (ALA-PDT) is a highly selective treatment for malignant cells. ALA-PDT has the potential to develop into a novel therapeutic strategy for various types of cancer. Recently, light-emitting diodes (LEDs), which are inexpensive, stable and easier to handle compared to lasers, have been used in PDT as a light source. However, in colorectal cancer (CRC), the efficacy of ALA-PDT in combination with LEDs has not been fully assessed. Therefore, in this study, we evaluated the antitumor effect of ALA-PDT using various LEDs in colon cancer cells. The HT-29 human colon cancer cell line was used both in vitro and in vivo. HT-29 cells were seeded in 96-well plates. Following 5-ALA administration, cells were irradiated using LEDs at different wavelengths. Three types of LEDs, blue (peak wavelength, 456 nm), white (broad-band) and red (635 nm) were used. Twenty-four hours after irradiation, the cytotoxic effects of ALA-PDT were measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. In order to evaluate the antitumor effect of ALA-PDT in vivo, nude mice were inoculated with HT-29 cells. Xenograft mice were injected intraperitoneally with 5-ALA and irradiated with 3 types of LEDs at a measured fluence rate of 96 mW/cm(2) and fluence of 32 J/cm(2). Each group comprised 6 mice. ALA-PDT was repeated 3 times at weekly intervals. Tumor weights were measured. Compared to the controls, ALA-PDT using LEDs showed significant antitumor effects in vitro and in vivo. The blue and white LEDs demonstrated greater antitumor effects compared to the red LEDs in vitro and in vivo. In particular, tumor inhibition rates in the blue and white LED groups were approximately 88% to those of the control group in the mouse models. In conclusion, ALA-PDT using LEDs is effective and useful in the treatment of CRC cells. This method could be a novel treatment modality for CRC.